The Digital Marketing Strategies of PT Bisa Artifisial Indonesia - Abdul Hardia Amin (PT SOLUSI EDUKASI BERDIKARI, 2024)
This internship report examines how digital marketing strategies impact the sales of frozen food products at Bisa Kitchen, which is part of the PT Bisa Artifisial Indonesia project. The results show effectiveness in utilizing social media platforms such as Instagram and TikTok and email marketing to increase brand awareness and customer engagement. However, the problems found include algorithm changes, limited resources, and competitive market competition. The strategic management implemented optimizes digital marketing efforts, expands customer relationships, and expands market reach. This strategy also ensures that Frozen Food Bisa Kitchen will continue to grow.